The Existence of The Main Character's Crime in The Short Stories of Berenice and The Tell-Tale Heart by Edgar Allan Poe - Nurelah, Ai; Pertala, Erik Chandra; Hestiana, Siska (Politeknik Siber Cerdika Internasional, 2023)
This study examines the existence of crimes committed by the protagonists of Edgar Allan Poe's short stories